2020
DOI: 10.3389/fmicb.2019.03002
|View full text |Cite
|
Sign up to set email alerts
|

Water Flow and Light Availability Influence on Intracellular Geosmin Production in River Biofilms

Abstract: Hydro-morphological alterations in water bodies caused by climate change and human activities affects the ecosystem functioning and generate important water quality problems. Some of these alterations can generate an increase in cyanobacterial blooms, which are associated with the appearance of bad taste and odorous compounds such as geosmin. The factors that trigger their production are still unclear, and this inability to predict geosmin episodes provokes economic problems for water supply companies. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Changes at the structural level were reflected in functional parameters with photosynthetic efficiency (Yeff) being significantly lower under low DIN:SRP ratio. This could be explained by the higher presence of cyanobacteria in these treatments, since some studies have found that cyanobacteria usually show low photosynthetic efficiency values compared with the rest of the algal community (Espinosa et al, 2020;Luimstra et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Changes at the structural level were reflected in functional parameters with photosynthetic efficiency (Yeff) being significantly lower under low DIN:SRP ratio. This could be explained by the higher presence of cyanobacteria in these treatments, since some studies have found that cyanobacteria usually show low photosynthetic efficiency values compared with the rest of the algal community (Espinosa et al, 2020;Luimstra et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The concentration of geosmin in biofilm was quantified following the protocol described by Espinosa et al (2020). Briefly, a headspace solid phase micro-extraction was performed.…”
Section: Geosminmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, each cobble was scrapped in 60 ml of water from the same sampling site to obtain a biofilm suspension. Aliquots of this suspension were used to analyze chlorophyll- a (Chl- a ), performed as described by Jeffrey and Humphrey (1975) , and ash-free dry mass as described in Espinosa et al (2020) . The Margalef index was also calculated as the quotient between the carotenoid/Chl- a ratio, being values obtained from the spectrophotometric reading of the sample at 430 nm (carotenoids and accessory pigments concentration) and 665 nm (Chl-a concentration), to obtain information about the maturity of the populations ( Elosegui and Sabater, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…This would agree with our study, where higher geosmin concentration was observed at lower temperatures (close to 10 • C), whereas at higher temperatures (20-25 • C), geosmin levels were below the detection limit (Figure 6B). Moreover, considering that low light conditions have been described to favor intracellular geosmin production in river biofilms (Espinosa et al, 2020), the increased light availability occurring in summer may be an additional limiting factor for microbial geosmin production in the Ter River, as higher light incidence prevents gaseous vacuoles formation and geosmin production (Li et al, 2012). In fact, different studies have shown that at temperatures ≈20-25 • C, higher light intensity hinders the production of geosmin by cyanobacteria (Oh et al, 2017;Alghanmi et al, 2018).…”
Section: Mismatch Between Cyanobacteria Abundance and Geosmin Concentrationmentioning
confidence: 99%